PENGARUH PENGEMBANGAN KARIR,MOTIVASI KERJA DAN KOMPETENSI TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PERUSAHAAN DAZZLE YOGYAKARTA - IRFAN MEDIANO SITEPU (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to determine the influence of the variable influence of career development, work motivation and work competence on employee work productivity at Dazzle company in Yogyakarta. This research method uses descriptive survey methods and explanatory surveys. The sample in this study were 50 respondents who were drawn from employees at the company Dazzle Yogyakarta. The data analysis method used in this study was multiple regression analysis. The result of the research is that there is a positive and significant influence on career development variables, work motivation and work competence on work productivity in the company Dazzle Yogyakarta